A flying success @ CAMAR - Faridah, Hamzah (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
22 May 2010. CMLHS extended its remarkable contribution to the society by organising a Let’s Read (Jom Membaca) programme which had taken place at Permata Camar Orphanage (CAMAR), Sungai Soi, Kuantan.